SEASONAL VARIATIONS OF BACTERIAL FLORA OF FRESH OIL SARDINES(Sardinella longiceps) - KARTHIAYANI, T C; IYER, K MAHADEVA (Fishery Technology, 2025)
An elaborate study was made on the qualitative andquantitative seasonal variations in the bacterial flora of fres.h oilsardines and their biochemical reactions. It was observed that thetotal bacterial loads and their phosphorescent and biochemicalcharacters were influenced by changes in seasons. During monsoonseason total bacterial count was high. Mesophiles predominatedduring summer, but phosphorescent bacteria were less. Winterfavoured the selection of biochemically less active groups ofbacteria.